(untitled) (Proceedings of the International Conference on Public Health, 2024)
Abstract World Health Organization reported on the global burden of food-borne diseases by stating that the high death rates in regions such as Africa, has the highest burden of food-borne diseases per population. The incident that occurred in Soweto and other parts of South Africa over the safety of food being sold at tuck shops led to community uproar and panic. The primary objective of the study was to assess the knowledge of tuck shop owners on food safety in relation to hygiene, food poisoning and Certificate of Acceptability (CoA). A quantitative cross-sectional study was used. Participants without Certificate of Acceptability were included. A self-administered questionnaire was used for data collection. The study population was 324 with a sample size of 100%. Data was captured into Microsoft Excel and exported to Statistical Package for Social Science (SPSS) for analysis. Tuck shop owners with primary and secondary education were significantly likely to be knowledgeable about food safety (OR) 5.88, 95%CI (2.34-14.63), (OR) 1.72, 95%CI (0.89-3.39). Participants who were purchasing food products at a retail shop or food warehouse with a Certificate of Acceptability (n=227; 70.1%) were significantly likely to be knowledgeable about food safety. The participants that did not know food poisoning were significantly more likely males in both crude odds ratio12.03 95% CI (2.87-50.48) and adjusted analysis AOR 8.91, 95% CI (1.89-42.08). About (n=84; 25.9%) of participants did not believe most deaths are also caused by food poisoning from poor hygiene (OR 8.80 95% CI (2.68-28.91) and AOR 8.67, 95%CI (1.83-40.85). The study has shown that tuck shops can be a public health threat in the community due to lack of knowledge of tuck shop owners on food safety and food poisoning which could lead to food poisoning outbreaks and subsequently death.